The Treaty of Nice : actor preferences, bargaining and institutional choice - Laursen, Finn (Constitutional law library ;, 2006)
Giving an analysis of the making of the Treaty of Nice, the treaty of the European Union, adopted in 2000. This book analyses the interests and strategies of the various actors, including the 15 Member States, during the negotiations and tries to explain the main institutional changes, such as the re-weighting of votes in the Council of Ministers.